The Effect of Capital Intensity, Executive Characteristics, and Profitability on Tax Avoidance, With Leverage as A Moderating Variable, in Manufacturing Companies in The Non-Consumer Sector – Cyclicals Listed on The IDX from 2023 to 2025 - Febi, Sisca Sisilia Cintia (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to analyze the influence of capital intensity, executive character, and profitability on tax avoidance with leverage as a moderation variable in manufacturing companies in the non-cyclical consumer sector listed on the Indonesia Stock Exchange for the 2023–2025 period. This study uses a quantitative method with secondary data obtained from the company’s annual financial statements. The sampling technique used purposive sampling so that as many as 52 manufacturing companies in the consumer non-cyclicals sector met the research criteria during the 2023–2025 period. The data analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of the SmartPLS application. The results of the study show that capital intensity has a positive effect on tax avoidance, while executive character and profitability have no effect on tax avoidance. In addition, leverage is able to moderate the effect of capital intensity on tax avoidance in a negative direction and is able to moderate the effect of profitability on tax avoidance in a positive direction. However, leverage is not able to moderate the influence of executive character on tax avoidance. Simultaneously, capital intensity, executive character, and profitability have an effect on tax avoidance in manufacturing companies in the non-cyclical consumer sector listed on the Indonesia Stock Exchange for the 2023–2025 period.